A Feedback Transformation of the Planning Problems. - Sierocki, Ireneusz (Applicable algebra in engineering, communication and computing.)
This paper proposes a problem transformation method, called feedback transformation method, for solving the planning problems. Some basic notions from the theory of problem transformation are introduced. Two measures of problem complexity are defined. Algebraic properties of the feedback transformation are investigated. Finally, a partial relationship between the problem transformation and decomposition methods is established.